Ilham Ramadan PRINSIP-PRINSIP PENDIDIKAN PERPEKTIF ALQURAN DAN HADIS - Ilham Ramadan Siregar (Al-Mu'tabar, 2022)
The principle of Islamic education is the main basis for human beings to carry out their main duties on earth either as caliph or position as a servant. As a caliph in charge of managing the earth, it is necessary to have several principles that become the basis or foundation in its implementation. So the way to obtain these principles is through Islamic education. Some principles of education, if traced from the development of early Islam as contained in the hadith of the Prophet, although the explanations are still very general, the Prophet, peace be upon him, has talked about them a lot. Both about principles in seeking knowledge and when conveying knowledge which is part of the educational process. With the principle of Islamic education based on the Qur'an and hadith as the main reference, it is hoped that Islamic education will be more focused and not lose its initial goal, which is to bring success in education which then brings goodness in the world and the hereafter.